Religious-Based Women’s Movement Typology in Modern Indonesia: West Java Experiences - Bintari, Antik; Widianingsih, Ida; Rahmatunnisa, Mudiyati (Universitas Muhammadiyah Tangerang, 2025)
This article aims to highlight the typology of faith-based women's movements and organizations in the democratic era. This research focuses on religious women's organizations in West Java, including representatives from Islam, Christianity, Catholicism, Hinduism, Buddhism, and indigenous beliefs. The purpose of this research is to determine the roles and strategies used by religious-based women's movements and organizations in advocating for civil society interests, particularly in promoting gender equality issues. The research results indicate that religious-based women's organizations or movements overall prioritize and consider religious values in their various actions and organizational decisions when advocating for gender equality issues. In West Java, religious-based women's movements and organizations exhibit various typologies, with some rooted in Islam. Three dominant typologies emerged from the organizations studied: religious-centered, religiously affiliated, and religiously backgrounded. These three typologies provide at least a glimpse of the differences and similarities in the strategies of women's movements and organizations in advocating for gender-responsive public interests, particularly how they collaborate with the government and other stakeholders.Artikel ini bertujuan untuk menyoroti tipologi gerakan dan organisasi perempuan berbasis agama di era demokrasi. Penelitian ini berfokus pada organisasi perempuan berbasis agama di Jawa Barat, yang meliputi perwakilan dari Islam, Kristen, Katolik, Hindu, Buddha, dan Penghayat.Tujuan penelitian ini adalah untuk menentukan peran dan strategi yang digunakan oleh gerakan dan organisasi perempuan berbasis agama dalam memperjuangkan kepentingan masyarakat sipil khususnya dalam memperjuangkan isu-isu kesetaraan gender. Hasil penelitian menunjukkan bahwa keseluruhan organisasi atau gerakan perempuan berbasis agama dalam memperjuangkan isu-isu kesetaraan gender tersebut dengan memprioritaskan dan mempertimbangkan nilai-nilai agama dalam berbagai tindakan dan keputusan organisasi. Di Jawa Barat, gerakan dan organisasi perempuan berbasis agama menunjukkan berbagai tipologi, dengan beberapa di antaranya berakar pada Islam. Tiga tipologi dominan muncul dari organisasi yang diteliti, yaitu tipologi berpusat pada agama, tipologi berafiliasi dengan agama, dan tipologi berlatar belakang agama. Ketiga tipologi ini setidaknya memberikan gambaran perbedaan dan persamaan strategi gerakan dan organisasi perempuan dalam memperjuangkan kepentingan publik yang responsive gender, khususnya bagaiamana mereka melakukan kolaborasi dengan pemerintah dan pemangku kepentingan lainnya.